Exploring small scale irrigation-nutrition linkages - Choufani, Jowel; Bryan, Elizabeth; Mekonnen, Dawit Kelemework; Ringler, Claudia (International Food Policy Research Institute, 2021)
The evidence on the potential for agricultural interventions to contribute to improved nutrition has grown considerably over the past decade (Ruel et al., 2018). Numerous studies have explored both positive and negative effects of agriculture on nutrition and health (Ruel and Alderman, 2013; Herforth and Harris, 2014; Masset et al., 2012; Hoddinott, 2012). However, as an important and growing component of agriculture, smallscale irrigation has not yet been given the attention it deserves. The Innovation Laboratory for Small Scale Irrigation (ILSSI) set out, among others, to fill the evidence gap on irrigation-nutrition linkages. Domènech (2015) describes several potential pathways through which irrigation can influence food security, nutrition, and health outcomes, including 1) a production pathway, 2) an income pathway, 3) a water supply pathway, and 4) a women’s empowerment pathway. To illustrate these pathways, we adapted the agriculturenutrition framework of Herforth and Harris (2014) to include irrigation (Figure 1), while also noting a fifth, negative pathway that links irrigation to water pollution and disease via the application of fertilizers and pesticides and via supporting vector-borne diseases, such as malaria or schistosomiasis, respectively (Passarelli et al., 2018).